Diagnosing Autism in the United Arab Emirates - Mahmoud, Mahmoud Mohamed Abdulrahim (2017)
Early identification and accurate diagnosis of autism improve the likelihood of favorable outcomes for children with Autism Spectrum Disorder (ASD). Thus, early identification and diagnosis of autism are gaining global attention. There are needs to avoid the negative implications of lack of diagnosis, misdiagnosing or over-diagnosing children with autism. The study aspires to contribute in improving the services for children in the United Arab Emirates (UAE) by examining the current situation, parents’ views, and other stakeholders’ views. The objective is to provide information that will help design better procedures in the country. A combination of surveys, interviews, and focus groups are used as sources of data for the study. This provides a view of the missing components and the challenges that is faced in the process. It provides insights into the difficulties, struggles, and gaps in the current system that need to be addressed to improve the services in the future. The study of the literature, identifying gaps in the development of diagnostic processes, diagnostic criteria, training and educating professionals need to be addressed to develop the process. This research pointed out concerns related to certain aspects of the service in the UAE. Some recommendations are outlined in the study to better enhance the services and to provide effective services for children with autism.